2015
DOI: 10.1007/s00244-015-0169-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Sources, and Potential Ecotoxicological Risk of Polycyclic Aromatic Hydrocarbons in Surface Sediments from Bahía Blanca Estuary, Argentina

Abstract: Thirty-four surface sediment samples were collected from Bahía Blanca Estuary, Argentina, to evaluate polycyclic aromatic hydrocarbon (PAH) contamination and ecotoxicity risk by applying sediment-quality guidelines (SQGs) and toxic equivalent factors (TEQ). Total concentrations of 17 parent PAHs, including the 16 United States Environmental Protection Agency priority PAHs, were measured using gas chromatography-mass spectrometry, and their levels ranged from 19.7 to 30,054.5 ng/g dry weight. The greatest value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(12 citation statements)
references
References 49 publications
0
11
0
1
Order By: Relevance
“…6). The average level of total TEQ PAHs found in sediment samples of the Tiber River and its Estuary was lower than in the sediments of Bahia Blanca, Argentina (Oliva et al, 2015) and in the sediments of Loire River, France (Bertrand et al, 2015); but were similar to those found in in the sediments of Mithi River, India (Singare, 2015) and the sediments of Cauca River, Colombia (Sarria-Villa et al, 2016). This showed that TEQ PAHs values of the Tiber River and its Estuary were in a low level and indicates that less ecological risk exists in the Tiber River basin.…”
Section: Ecological Risk Assessmentmentioning
confidence: 56%
See 1 more Smart Citation
“…6). The average level of total TEQ PAHs found in sediment samples of the Tiber River and its Estuary was lower than in the sediments of Bahia Blanca, Argentina (Oliva et al, 2015) and in the sediments of Loire River, France (Bertrand et al, 2015); but were similar to those found in in the sediments of Mithi River, India (Singare, 2015) and the sediments of Cauca River, Colombia (Sarria-Villa et al, 2016). This showed that TEQ PAHs values of the Tiber River and its Estuary were in a low level and indicates that less ecological risk exists in the Tiber River basin.…”
Section: Ecological Risk Assessmentmentioning
confidence: 56%
“…pyrolytic, petrogenic and diagenetic) gives rise to typical PAH patterns. In general, combustion products are dominated by relatively high molecular weight (HMW) compounds with four or more condensed aromatic rings, whereas bi-and tricyclic aromatic compounds (LMW) are more abundant in fossil fuels, which are, moreover, dominated by alkylated derivatives Oliva et al, 2015;Wu et al, 2015). Using chemical profiling and particular compound ratios, it is possible to recognize the processes that generate these compounds (Baumard et al, 1998;Yunker et al, 2002).…”
Section: Source Identificationmentioning
confidence: 99%
“…Under the Canadian criteria of ERL (4022 ng/g) and ERM (44,792 ng/g) (Long et al, 1995), all of the PAHs were lower than the ERL. Also, PAHs concentrations were at lower level in Yellow River estuarine compared with relevant areas worldwide in the published reports (Oliva et al, 2015). Compared soil PAHs in the YRD region with in some developed regions in China, concentrations were much lower than that in Beijing (suburban topsoil, 16-3884 ng/g) (Ma et al, 2005), Hangzhou (59.71-615.8 ng/g) (Chen et al, 2004), and Hong Kong (urban soil 16 PAHs was 42.9-410 ng/g) (Zhang et al, 2006), but much larger than uncontaminated soil PAHs levels required by the Dutch government (20.0-50.0 ng/g) (Van Brummelen et al, 1996).…”
mentioning
confidence: 79%
“…With an area of 2200 km 2 , the watershed of the YRD is the largest and youngest wetland in the warm temperate zone of China (Yuan et al, 2012), and is also the youngest land in the world. Extremely high sediment loads (N1000 million tons per year, Mt/year) have been discharged to the sea over thousands of years as a result of poor agricultural practices in the Loess region (Oliva et al, 2015). High sediment loading from the river and transport by hyperpycnal flows into the estuary have made considerable contributions to the deltaic depositional system (Fan et al, 2009).…”
mentioning
confidence: 99%
“…In comparison with polluted rivers in other parts of the world ( [30], and in the Sarno River by Montuori and Triassi [22]. The concentration of ΣPAHs in the samples of sediment from the Volturno River and river mouth was inferior than the concentration found in the Daliao River, China by Guo et al [46], in the Caspian sea coast, India by Yancheshmeh et al [68], in the Ba n Bay, Canada by Foster et al [69], in the Cocó and Ceará Rivers, Brazil by Cavalcante et al [70], in the Bahia Blanca Estuary, Argentina by Oliva et al [10], in the Cauca River, Colombia by Sarria-Villa et al [8], in the Buffalo River Estuary, South Africa by Adeniji et al [52], in the Ammer River, Germany by Liu et al [9], in the Portimão Harbor, Portugal by Bebianno et al…”
Section: Pahs Concentrations In Sedimentsmentioning
confidence: 92%